A provably secure certificateless public key encryption with keyword search. (2nd January 2019) - Wu, Tsu-Yang; Chen, Chien-Ming; Wang, King-Hang; Meng, Chao; Wang, Eric Ke
ABSTRACT: Public key encryption with keyword search, known as PEKS, is a useful technology in some Storage-as-a-Service clouds. This technology allows the cloud server to search on a keyword, which is received from the data owner/user, over encrypted data without having the ability to decrypt the stored data. PEKS with designated verifier, known as dPEKS, further advances the security of PEKS such that only a designated server can perform the keyword searching. Combining the certificateless technology, which aims to avoid the key escrow problem in ID-based cryptography, produces a certificateless dPEKS scheme that inherits the property of certificatelessness in key management in the dPEKS. This paper presents a provably secure certificateless dPEKS which has fixed an insecure scheme which was proposed earlier. The scheme presented in this paper is proven to be secure under Bilinear Diffie–Hellman problem.